Poder e políticas públicas nos municípios que integram o Arranjo Produtivo Local (APL) de metais sanitários no Noroeste do Paraná - Ferreira, Joyce Allane Apolinário (2013)
Since 1990, the theme Local Productive Arrangement (LPA) has become important in economic literature and specially in the guidelines of public policies concerning local and regional development. After the decade of 1990, public policies are built in Brazil aiming to support the LPAs, encouraged by the fact that they could strengthen local development. In Paraná, the creation of the LPA network was the beginning of the use of public policies for the LPA in the state. This is due to the fact that it gained the role of managing these policies through unions with other institutions (SEPL, Sebrae and Fiep). In 2005, with a project coordenated by SEPL and IPARDES 22 LPAs were identified, amongst them the LPA of Sanitary Metals in the Northwest region, consisting of companies from Loanda, Santa Cruz de Monte Castelo, Santa Isabel do Ivaí and São Pedro do Paraná. The growing number of companies in this LPA has allowed emphasis on the paranaense's production of sanitary metals on state and national levels, ranking second in establishing jobs, being behind only of the state of São Paulo. According to data from RAIS, the Ministry of Labour and Employment (MLE), until December of 2011, there were 64 establishments in Paraná, that were ranked in the national economic activities CNAE 2913 (the production of faucets and valves) and, 50 of these were found in the cities of the Sanitary Metals' LPA, in other words 78,12% of the establishments were connected with this group. Facing the economical and political importance of this LPA for this region, this work consists on analyzing the public policies of the local development from the LPAs and the Power relations of the cities that are part of the LPA of Sanitary Metals in the Northwest of Paraná. For the development of this work literature review concerning the concepts of Power, public policies, local developlment and Productive Arrangement was used. For the gathering of data, field work was done in the towns of LPA, a questionnaire was given to 10 companies and with the public Power of the towns. The relationship of local public Power of some companies pointed out to be conflictual, but it also showed that other companies cooperate with local public Power, in which it can be considered that the individual interest grows according to the LPA's interest.